Proteomic Dissection of Seed Germination and Seedling Establishment in Brassica napus - Gu, Jianwei; Chao, Hongbo; Gan, Lu; Guo, Liangxing; Zhang, Kai; Li, Yonghong; Wang, Hao; Raboanatahiry, Nadia; Li, Maoteng (Frontiers in Plant Science, 2016)
The success of seed germination and establishment of a normal seedling are key determinants of plant species propagation. At present, only a few studies have focused on the genetic control of seed germination by using a proteomic approach in Brassica napus. In the present study, the protein expression pattern of seed germination was investigated using differential fluorescence two-dimensional gel electrophoresis in B. napus. One hundred and thirteen differentially expressed proteins (DEPs) that were mainly involved in storage (23.4%), energy metabolism (18.9%), protein metabolism (16.2%), defense/disease (12.6%), seed maturation (11.7%), carbohydrate metabolism (4.5%), lipid metabolism (4.5%), amino acids metabolism (3.6%), cell growth/division (3.6%), and some unclear functions (2.7%) were observed by proteomic analysis. Seventeen genes corresponding to 11 DEPs were identified within or near the associated linkage disequilibrium regions related to seed germination and vigor quantitative traits reported in B. napus in previous studies. The expression pattern of proteins showed that heterotrophic metabolism could be activated in the process of seed germination and that the onset of defense mechanisms might start during seed germination. These findings will help generate a more in-depth understanding of the mobilization of seed storage reserves and regulation mechanisms of the germination process in B. napus.